2013
DOI: 10.1161/strokeaha.113.002493
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics and Outcomes Among Patients Transferred to a Regional Comprehensive Stroke Center for Tertiary Care

Abstract: Background and Purpose— Many patients are transferred to comprehensive stroke centers for advanced acute ischemic stroke care, especially after intravenous tissue plasminogen activator. We sought to determine differences in the baseline characteristics and outcomes between patients with acute ischemic stroke presenting directly to our academic stroke center’s front door versus transfers-in from another acute care hospital. Methods— Using our institution… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
27
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(28 citation statements)
references
References 16 publications
1
27
0
Order By: Relevance
“…14,15 Similarly, a recent study of acute ischemic stroke patients transferred to a comprehensive stroke center in Boston found that despite transferred patients having higher stroke severity, mortality and discharge disposition were similar to regular admissions. 10 However, this study population was limited to a large specialized center that provides extensive tele-stroke services; the proportion of transferred cases (55%) was, therefore, substantially higher than observed in this study (19%). To our knowledge, no other registry-based studies have reported on the outcomes and characteristics of acute stroke patients who have been transferred to registry hospitals.…”
Section: Discussionmentioning
confidence: 54%
See 3 more Smart Citations
“…14,15 Similarly, a recent study of acute ischemic stroke patients transferred to a comprehensive stroke center in Boston found that despite transferred patients having higher stroke severity, mortality and discharge disposition were similar to regular admissions. 10 However, this study population was limited to a large specialized center that provides extensive tele-stroke services; the proportion of transferred cases (55%) was, therefore, substantially higher than observed in this study (19%). To our knowledge, no other registry-based studies have reported on the outcomes and characteristics of acute stroke patients who have been transferred to registry hospitals.…”
Section: Discussionmentioning
confidence: 54%
“…However, for mortality at least, the association between being transferred and higher mortality was seen only among ischemic stroke and not hemorrhagic stroke patients. Few studies have described the characteristics and outcomes of acute stroke patients who are transferred between hospital, 9,10,14,15 and most of these studies have been from single referral centers. Two studies that assessed the effect of interhospital transfer in hemorrhagic stroke patients found similar rates of mortality and complications among patients who were transferred compared with direct admissions.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…[1,9,10] International and local data have shown that outcomes improve when patients are referred to regional specialised centres where a multidisciplinary team may manage their ailment. [11][12][13] For this reason, many patients will require CCT. In SA, paramedics currently do not have additional training to undertake these specialised transfers.…”
Section: Discussionmentioning
confidence: 99%